Digital Leadership: Comparative Study of Ridwan Kamil and Wahidin Halim in Government Digitalization - Nurrohman, Bayu; Ramadhan, Gilang (International Journal of Demos (IJD), 2024)
AbstractThis research will photograph how digital leadership is carried out by regional heads in two provinces, namely the Governor of West Java, Ridwan Kamil, and the Governor of Banten, Wahidin Halim. These two figures will be compared from the perspective of digital leadership in administering government in their respective regions. This research will also photograph the achievements of each region in implementing electronic-based government. It is hoped that this research will be able to provide an overview of how digital leadership capabilities have a big impact on the implementation of government digitalization in the regional government organizations they lead. This research uses a qualitative method with a case study approach. The research results illustrate that the two former governors have similarities. Every leader has a vital role and real contribution in encouraging the digitalization of government with the digital resources and capabilities they have. The various appreciations received by both individuals and regional government organizations are clear evidence that their performance in driving digital transformation is recognized by many people as leaders who have good digital abilities and competencies.Keywords: Leadership, Digital Leadership, Banten Province, West Java ProvinceÂ AbstrakRiset ini akan memotret bagaimana kepemimpinan digital yang dilakukan oleh kepala daerah di dua Provinsi yaitu Gubernur Jawa Barat yaitu Ridwan Kamil dengan Gubernur Banten yaitu Wahidin Halim. Kedua tokoh ini akan dikomparasi dari sudut pandang kepemimpinan digital dalam penyelenggaraan pemerintahan di daerah masing-masing. Riset ini juga akan memotret pencapaian daerah masing-masing dalam menyelenggarakan pemerintahan berbasis elektronik. Diharapkan riset ini mampu memberikan gambaran tentang bagaimana kemampuan kepemimpinan digital sangat berdampak pada penyelenggaraan digitalisasi pemerintahan pada organisasi pemerintahan daerah yang dipimpin. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Hasil penelitian menggambarkan bahwa kedua Mantan Gubernur terdapat persamaan. Setiap pemimpin memiliki peran yang vital dan kontribusi yang nyata dalam mendorong terselenggaranya dgitalisasi pemerintahan dengan sumber daya dan kemampuan digital yang dimiliki. Berbagai apresiasi yang didapatkan yang diterima baik individu maupun oraganisasi pemerintahan daerah menjadi salah satu bukti nyata bahwa kinerja keduanya dalam mendorong transformasi digital diaku oleh banyak masyarakat sebagai pemimpin yang memiliki kemampuan dan kompetensi digital yang baik.Kata kunci:Kepemimpinan, Kepemimpinan Digital, Provinsi Banten, Provinsi Jawa Barat